2016
DOI: 10.1182/blood-2016-03-704023
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide-bendamustine-rituximab in patients older than 65 years with untreated mantle cell lymphoma

Abstract: Key Points Addition of lenalidomide to R-B is highly active in patients with untreated MCL, but associated with unexpected high rates of infections and SPMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 35 publications
1
54
0
Order By: Relevance
“…In the Nordic MCL4 study, after 6 cycles of rituximab, bendamustine, and lenalidomide, the percentage of patients among 32 evaluable patients who were MRD positive by qualitative nested PCR was 56% in BM and 61% in PB. 26 In a smaller phase 2 study, clonotypes for MRD assessment were identified by HTS in 19 of 23 patients, and 77% of 13 patients with PB samples were MRD negative by HTS after 3 cycles of R-bendamustine. 27 To the best of our knowledge, there are no currently available data regarding the effects of new targeted treatment drugs such as ibrutinib on MRD in MCL.…”
Section: Mrd During and After Induction Treatmentmentioning
confidence: 99%
“…In the Nordic MCL4 study, after 6 cycles of rituximab, bendamustine, and lenalidomide, the percentage of patients among 32 evaluable patients who were MRD positive by qualitative nested PCR was 56% in BM and 61% in PB. 26 In a smaller phase 2 study, clonotypes for MRD assessment were identified by HTS in 19 of 23 patients, and 77% of 13 patients with PB samples were MRD negative by HTS after 3 cycles of R-bendamustine. 27 To the best of our knowledge, there are no currently available data regarding the effects of new targeted treatment drugs such as ibrutinib on MRD in MCL.…”
Section: Mrd During and After Induction Treatmentmentioning
confidence: 99%
“…In a retrospective cohort study of myelodysplastic syndrome (MDS) patients, lenalidomide was not associated with an increased risk of SPM or transformation to AML [194]. Finally, a recent report of lenalidomide with rituximab and bendamustine as first line therapy for elderly mantle cell lymphoma patients showed a higher number of SPMs than expected, with 9 SPMs in 8 patients (16%) including 2 hematologic and 5 solid tumors [195]. …”
Section: Imids and Second Primary Malignanciesmentioning
confidence: 99%
“…It is a CD20‐specific monoclonal antibody which depletes peripheral blood B cells and can also cause prolonged hypogammaglobuinaemia, predisposing to infections . All reported cases of necrotising retinitis in patients who were on rituximab had complicating factors such as concurrent other intensive immunosuppression and corticosteroid therapy . Most cases were of CMV retinitis, with one case each of ARN and PORN .…”
Section: Biologic Therapy and Viral Retinitismentioning
confidence: 99%